Efficacy and safety of repetitive transcranial magnetic stimulation in the treatment of male smokers with tobacco use disorder: a randomized controlled trial - Salma W. Mousa; Adel A. Badawy; Gehan F. Attia; Wesam A. Ghareeb (Middle East Current Psychiatry, 2025)
Abstract Background Tobacco use disorder (TUD) is a long-term condition marked by compulsive smoking, intense cravings, and withdrawal effects. Repetitive transcranial magnetic stimulation (r-TMS), which targets the left dorsolateral prefrontal cortex (DLPFC), has been identified as a promising therapeutic approach. However, research on the use of r-TMS for treating TUD in Egypt remains scarce. This study aimed to assess the effectiveness of active r-TMS in reducing smoking behavior, withdrawal symptoms, cravings, and nicotine dependence, in comparison to sham treatment, while also examining its tolerability as a treatment option for TUD. Results Forty male smokers (aged 18–60 years) who smoked a minimum of 10 cigarettes per day for a minimum of 12 months were randomized into two groups: the active r-TMS group (n = 20) and the sham group (n = 20). Active r-TMS treatment, delivered over 15 sessions (5 sessions weekly for 3 consecutive weeks), significantly reduced the number of cigarettes smoked daily (p = 0.001), nicotine dependence (p = 0.023), withdrawal symptoms (both self-reported and observer-rated) (p = 0.001), and craving (p = 0.007) compared to the sham treatment. Urinary cotinine levels, a biomarker of nicotine intake, were also significantly lower in the active r-TMS group during the follow-up period (p = 0.011). The treatment was generally well-tolerated, with only minor side effects, such as headaches (22.5%). Conclusions Active r-TMS targeting the left DLPFC effectively reduced nicotine dependence, withdrawal symptoms, and craving, demonstrating its potential as a promising treatment for TUD. These findings align with previous studies supporting the efficacy of r-TMS in addiction treatment. Further research is needed to optimize treatment protocols, explore combined therapies, and assess long-term outcomes to improve smoking cessation in diverse populations.